PENDEKATAN TAFSIR EKONOMI KONTEMPORER DALAM MEMAHAMI AYAT-AYAT EKONOMI AL-QUR’AN - Saeed Hayat; Halimah Basri; Aisyah Arsyad; fatimah (IMTIYAZ: Jurnal Ilmu Keislaman, 2026)
This research aims to analyze contemporary economic interpretation approaches in understanding the economic verses of the Koran contextually and applicatively. The research uses qualitative methods with the type of library research through a thematic interpretation approach (maudhu'i) combined with contextual analysis of modern economic dynamics. The research results show that contemporary economic interpretation is an integrative approach that connects the values ​​of the Al-Qur'an with modern economic realities through a combination of the maudhu'i method and the adabi ijtima'i style. This approach produces an understanding of economic verses that is more systematic, contextual, and relevant to modern economic problems. This research also shows that the economic verses of the Koran contain the main principles of justice (al-'adl), balance (tawazun), and social responsibility (mas'uliyyah) as the basis for building a just and sustainable Islamic economic system. Thus, contemporary economic interpretation not only functions as an interpretive method, but also as an epistemological framework in the development of modern Islamic economics